Large ovarian endometriomas are associated with high pre-operative anti-Müllerian hormone concentrations. Issue 1 (January 2021) - Roman, Horace; Chanavaz-Lacheray, Isabella; Mircea, Oana; Berby, Benoit; Dehan, Lise; Braund, Sophia; Verspyck, Eric; Puscasiu, Lucian
Abstract: Research question: Are large ovarian endometriomas associated with high pre-operative anti-Müllerian hormone (AMH) concentrations? Design: Data from 332 women who underwent AMH measurement before surgery for endometriosis were prospectively recorded in a large database. Univariate analysis compared AMH concentrations in terms of the patients' baseline characteristics. A multivariate model was used to identify variables having an independent relationship with AMH concentration. Results: Among 332 women included in the study, 47.6% were aged 18–30 years, 67.8% were infertile and 85.5% were nulliparous. A total of 66.3% had ovarian endometriomas, and 10.8% had cysts measuring over 6 cm. Bilateral cysts over 3 cm were recorded in 24.7% of the women. Univariate analysis identified two variables that had a statistically significant relationship with AMH concentration: the woman's age ( P  = 0.01) and cyst size ( P  < 0.001). Multivariate analysis revealed that ages of 36–40 years and over 40 years showed a significant association with lower AMH concentrations ( P  = 0.02 and P  = 0.009, respectively), while a cyst size of over 6 cm was statistically associated with high AMH concentrations ( P  < 0.001), after adjustment for smoking, parity, rectosigmoid endometriotic nodules and a bilateral location of endometriomas. Conclusions: Pre-operative AMH concentration was significantly increased in women with large endometriomas of over 6 cm, independent of their age or the presence of bilateral endometriomas. This is relevant for both surgeons and patients when planning surgery in women with an intention to conceive post-operatively.